Studi Struktur mikro Silikon dalam Paduan Aluminium-Silikon pada Piston dari Berbagai Merek Sepeda Motor - Tjokorda Gde Tirta Nindhia (Jurnal Energi Dan Manufaktur, 2010)
This research introduce microstructure of silicon in aluminium-silicon alloys that were collected from varietymanufacture company that available in Indonesia such as Vespa, Suzuki, Kawasaki, Honda, and Yamaha. The microstructureobservation was conducted followed standard metallurgy test for aluminium. The result is presented in the form of metallographicfrom each specimen followed by literature study to obtain information regarding process and its properties related withapplication as a piston. It is revealed from this observation that the microstructure of silicon was found vary depend on whichcompany it’s coming from. The primarily differences were found from the silicon size and the texture. These differences makeeach piston having its own characteristic and properties that make it different one another related to wear resistance